2010
DOI: 10.1016/j.puhe.2010.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of country of study on student responsiveness to the H1N1 pandemic

Abstract: Students' responses towards university pandemic measures were largely positive, but sensitivity towards these measures varied between groups by country of study. This should be considered in further comparative studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The level of knowledge about the symptoms of the disease was not good enough, except for high fever and fatique. Hand washing was the most reported measure like other studies, although Griffiths et al showed that student responsiveness to H1N1 pandemics and sensitivity towards these measures like hand washing may differ from country to country [11][12][13]. However, there was an approximately 5.0% antibiotic usage for both groups, which is not appropriate.…”
Section: Discussionmentioning
confidence: 83%
“…The level of knowledge about the symptoms of the disease was not good enough, except for high fever and fatique. Hand washing was the most reported measure like other studies, although Griffiths et al showed that student responsiveness to H1N1 pandemics and sensitivity towards these measures like hand washing may differ from country to country [11][12][13]. However, there was an approximately 5.0% antibiotic usage for both groups, which is not appropriate.…”
Section: Discussionmentioning
confidence: 83%
“…When antivirals were prescribed as prophylaxis for influenza A(H1N1)pdm09, the only demographic predictor of adherence was sex, with male students being more likely to take oseltamivir than female students . Other predictors included an earlier time in the pandemic, country of study (higher adherence in students studying in Singapore than those studying in the United States), previous compliance with other precautionary advice about pandemic flu, beliefs that the recommended preventative measures were necessary and having discussed taking oseltamivir with someone who had not experienced side effects . Where antivirals were prescribed as prophylaxis for avian influenza (H7N3), having had direct contact with infected poultry was a significant predictor for adherence to antivirals …”
Section: Resultsmentioning
confidence: 99%
“…Identifying predictors of adherence can help to inform areas which can be targeted to improve adherence further still. Attempts to identify demographic predictors of adherence have given mixed results, with male sex being found as a predictor for actual adherence in summer school students and female sex being found as a predictor of intended adherence in the Singaporean military . Age was also a predictor of actual adherence with oseltamivir during the 2009/2010 influenza pandemic, with higher adherence seen in people with an influenza diagnosis in Norway aged under 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of mask wearing in these students was lower than that in Hong Kong and Singapore university students during the H1N1 pandemic. 7 Female students were more likely than male students to adopt preventive precautions, likely related to the higher perceptions of H1N1 risk reported by females. 8 Furthermore, adoption of H1N1 preventive precautions was associated with better knowledge of transmission and perceived high risks of infection, as found in the Western 9 and Chinese 10 general populations.…”
Section: Discussionmentioning
confidence: 99%